(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
The green color represents the environmentally friendly aspects that have become one of the most common and latest emerging trends. The individuals in the society have been founding different ways of adopting the green concept and contributing to creating a green environment. The significant aspect behind the green concept involves the reduction of waste materials from the environment and the conservation of energy and resources. On the same lines, green hospitals are becoming the need of the hour. The present study investigates factors affecting the adoption of Green hospitals among healthcare professionals. The study used a purposive sampling technique, and a sample of 300 healthcare professionals was taken from the National Capital Region (NCR) of India. Exploratory factor analysis explored four factors, namely, Usefulness, Ease of use, Ratings and Rankings, and Environment Friendly, that act as motivators for adopting green hospitals among healthcare professionals. Out of these factors, Environment friendly was the most contributing factor. The study has both managerial as well as social implications.